2017
DOI: 10.1016/j.micpath.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Acyl homoserine lactone changes the abundance of proteins and the levels of organic acids associated with stationary phase in Salmonella Enteritidis

Abstract: Quorum sensing (QS) is cell-cell communication mechanism mediated by signaling molecules known as autoinducers (AIs) that lead to differential gene expression. Salmonella is unable to synthesize the AI-1 acyl homoserine lactone (AHL), but is able to recognize AHLs produced by other microorganisms through SdiA protein. Our study aimed to evaluate the influence of AI-1 on the abundance of proteins and the levels of organic acids of Salmonella Enteritidis. The presence of N-dodecyl-homoserine lactone (C12-HSL) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…Based on these similarities, these results suggest that AI-1 can anticipate a stationary phase response. Moreover, these results corroborate our previous observation, in which the differentially abundant proteins and organic acids of Salmonella cultivated for 7 h in the presence of C12-HSL correlated with entry into the stationary phase of growth, mainly in relation to nitrogen and amino acid starvation as well as acid stress [ 35 ]. Schuster et al [ 36 ] showed that genes with expression influenced by the growth phase in P .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Based on these similarities, these results suggest that AI-1 can anticipate a stationary phase response. Moreover, these results corroborate our previous observation, in which the differentially abundant proteins and organic acids of Salmonella cultivated for 7 h in the presence of C12-HSL correlated with entry into the stationary phase of growth, mainly in relation to nitrogen and amino acid starvation as well as acid stress [ 35 ]. Schuster et al [ 36 ] showed that genes with expression influenced by the growth phase in P .…”
Section: Resultssupporting
confidence: 90%
“…Inoculum was prepared according to Almeida et al [ 35 , 41 ]. Tryptone soy broth (TSB; Sigma-Aldrich, India) was prepared with CO 2 under O 2 -free conditions, dispensed in anaerobic bottles that were sealed with butyl rubber stoppers and then autoclaved (anaerobic TSB).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behavior was observed in the etiological agent of bubonic plague Yersinia pestis , in which RNAseq analyses demonstrated that the ptsI gene was downregulated in the wild-type compared to an AHL-null strain during the logarithmic growth phase ( LaRock et al, 2013 ). The equal glucose absorption levels after 7 h of cultivation ( Figure 1 ) can be justified by a 1.57-fold increase in the abundance of PtsI protein (phosphoenolpyruvate protein phosphotransferase) in Salmonella Enteritidis PT4 578 at the same time and cultivation in TSB anaerobic medium supplemented with C12-HSL reported by Almeida et al (2017a) .…”
Section: Discussionmentioning
confidence: 73%
“…Besides C12-HSL, other AHLs tested did not influence the growth of Salmonella Enteritidis PT4 578 cultivated in anaerobic Tryptic Soy Broth (TSB) medium at 37°C ( Campos-Galvão et al, 2015 ; Almeida et al, 2017b ). Cultivation of Salmonella Enteritidis PT4 578 in anaerobic TSB medium supplemented with C12-HSL also led to alterations in protein abundance and levels of organic acids associated with the early stationary phase of growth ( Almeida et al, 2017a ). It also increases the expression of thiol-related proteins and thiol, as well as the alteration in the fatty acid profile ( Almeida et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%